A stratified ultrafast outflow in 1H0707−495?. Issue 1 (25th August 2018) - Kosec, P; Buisson, D J K; Parker, M L; Pinto, C; Fabian, A C; Walton, D J
ABSTRACT: Ultrafast outflows (UFOs) have recently been found in the spectra of a number of active galactic nuclei (AGN) and are strong candidates for driving AGN feedback. 1H0707−495 is a highly accreting narrow line Seyfert 1 and the second most X-ray variable bright AGN. Previous studies found evidence of blueshifted absorption at 0.1−0.2c in its spectrum. We perform a flux-resolved analysis of the full XMM−Newton data set on this AGN using both CCD and grating data, focusing on the low flux spectrum. We find strong evidence for a UFO in absorption at ∼0.13c, with an ionization parameter log (ξ/erg cm s −1 ) = 4.3. Surprisingly, we also detect blueshifted photoionized emission, with the velocity increasing at higher ionization states, consistent with a trend that has been observed in the UV spectrum of this object. The bulk of the X-ray emitting material is moving at a velocity of 8000 km s −1, with ionization parameter log (ξ/erg cm s −1 ) = 2.4. The wind kinetic power inferred from the UFO absorption is comparable to that of the UV and X-ray emission features despite their different velocities and ionization states, suggesting that we are viewing an energy-conserving wind slowing down and cooling at larger distances from the AGN.